Extradigital Glomus Tumor at the Elbow - Lucas Van Houtven; Dieter Peeters; Filip M. Vanhoenacker (Journal of the Belgian Society of Radiology)
Teaching point: Extradigital glomus tumor should be considered in the differential diagnosis of a highly vascular solid lesion that is painful on palpation.